A study of morbidity and mortality pattern of pre-term neonates in neonatal intensive care unit of a tertiary care hospital of North East India - Kalita, Dulal; Rahman , Mahibur; Barman, Diganta (Asian Journal of Medical Sciences, 2023)
Background: Pre-maturity is one of the major health problems and associated with high morbidities and mortality. According to the WHO every year, an estimated 15 million babies are born pre-term and this number is rising. Aims and Objectives: The objectives of the study were to know the various morbidity pattern developed during the clinical course and to identify the cause of mortality of pre-term babies admitted in neonatal intensive care unit (NICU). Materials and Methods: This prospective, observational study was conducted in the Neonatal Intensive Care Unit of Gauhati Medical College and Hospital, Assam, over a period of 1 year. A sample size of 150 pre-term babies selected randomly as per inclusion and exclusion criteria. Results: The total number of cases studied in the present study were 150 pre-term babies admitted in NICU. Male pre-term babies were 82 (54.6%) and female pre-term babies were 68 (45.3%). The various morbidities observed among the pre-term babies during the study period were neonatal hyperbilirubinemia (48%) followed by respiratory distress syndrome (RDS) (30%), neonatal sepsis (22%), hypocalcemia (16%), hypothermia (14.7%), necrotizing enterocolitis (NEC) (5.3%), and intraventricular hemorrhage (4.7%). The overall mortality among the studied cases was 12.6%. Out of 150 cases, 19 cases were expired (12.6%). The present study shows that RDS (36.8%), neonatal sepsis (26.3%), birth asphyxia (21.1%), and NEC (15.7%) were the major causes of mortality among pre-term babies. Conclusion: The survival rate increases significantly with increase in birth weight and gestational age. RDS, birth asphyxia, and neonatal sepsis were the leading causes of death.